Diagnostic ability of salivary matrix metalloproteinase‐9 lateral flow test point‐of‐care test for periodontitis. (26th October 2020) - Kim, Hyun‐Duck; Lee, Chang‐Soo; Cho, Hyun‐Jae; Jeon, Sumin; Choi, Young‐Nim; Kim, SungTae; Kim, DanHee; Jin Lee, Hyun; Vu, Huong; Jeong, Hee‐Jin; Kim, ByungGee
Abstract: Aim: This cross‐sectional study aimed to examine the diagnostic ability of salivary matrix metalloproteinase (MMP)‐9 lateral flow test (LFT) point‐of‐care (POC) kit and develop an algorithm for diagnosis of periodontitis. Materials and Methods: Through Seoul National Dental Hospital, 137 participants (46 LFT negatives, 91 LFT positives) were recruited. For salivary diagnostics, 150 μl of the unstimulated saliva was applied to LFT‐POC kit. To make a diagnosis of periodontitis, stage II‐IV in modified new international classification system was used. Covariates encompassing age, sex, smoking and obesity were evaluated through face‐to‐face interview. Enzyme‐linked immunosorbent assay was used for quantification of salivary MMP‐9. To develop a diagnostic algorithm, multivariable logistic regression analysis was used. Receiver operating characteristic curve was applied for evaluating diagnostic ability. Results: Diagnostic ability of salivary MMP‐9 LFT‐POC test was 0.82 (sensitivity of 0.92, specificity of 0.72) in total participants. Diagnostic algorithm using POC test resulted in a response equation, that is algorithm score = −3.675 + 2.877*LFT + 0.034*age + 0.121*sex + 0.372*smoking + 0.192*obesity. Diagnostic ability of the algorithm was 0.88 (sensitivity of 0.92, specificity of 0.85) with cut‐off score of 0.589. Conclusions: Salivary MMP‐9 LFT‐POC kit showed appropriate diagnostic ability for periodontitis and would be an efficient tool for screening of periodontitis.